Alignment of healthcare training criteria in Ukraine with european standards - Dvulit, I.; Dymar, N.; Kuzyk, P.; Marush, I.; Chugin, S. V.; Чугін, Сергій Вячеславович (My University, 2025)
Introduction: Providing medical care for the population in the context of modern societal development requires a constant review of specialist training standards in medicine. Currently, Ukraine is undergoing a process of harmonising its medical education standards with European requirements, which is an important step towards integration into the common European educational space and ensuring a high quality of medical personnel training. The study aimed to analyze the key aspects of harmonising medical education in Ukraine with European standards and the challenges and prospects of this process at the current stage of societal development. Methods: To create a narrative review, we implemented a bibliographic method to gather and analyze the relevant literature. Results: As a result of the research, it was identified that the most significant changes needed in the harmonisation process concern educational programmes, postgraduate education, and the accreditation system. Conclusions: Now, medical education has a promising future. Firstly, the balance between theoretical training and practical learning of higher education students is to be improved, the postgraduate education and certification system of doctors is to be developed, international cooperation and mobility programmes to be carried out, and finally, medical education to have improved infrastructure and funding.
Keywords: critical thinking; medical students; problembased learning; case method